DETECT DIARRHEAGENIC STRAIN OF ESCHERICHIA COLI IN CHILDREN UNDER FIVE YEARS - Resercher -Rahma Salah Talha; Supervised -Nihad Abdulhussain Jafar (European Science Publishing, 2024)
Aim: To determine the type of bacteria in human that cause diarrhea. using the multiplex pcr technique to identify strains Material method: This study includes100 samples for children under the age of 5, collected from Tikrit Teaching Hospital, the samples were transferred to the laboratory, and all bacterial isolates were diagnosed based on microscopic and phenotypic characteristics and biochemical tests. Results: E. coli bacteria was present, in addition to the presence of other types. The E. coli bacteria recorded the highest percentage of 59 (47%) of the bacterial isolates followed by Proteus spp. which recorded 36 (26%), while both bacterial isolates of Pseudomonas spp. and Salmonella enterica 18 (13%) and 8 (5%), respectively in the current study, about 78 (56%) stool samples from children under five years of age suffering from diarrhea were analyzed for the detection of E. coli strains. There were 56% of the isolates containing the uid A gene which confirms the detection and finding of E. coli. When determining the pathological patterns of the positive samples by cultural, biochemical tests, and by Multiplex PCR assay for the uid A gene, they were all positive. The type of strains causing diarrhea isolated from children's stool samples is shown in Figure (4-5), where the genes indicate that the strains of E. coli isolates causing diarrhea were ETEC and EHEC. Among the E. coli isolates detected, 64 (82%) belonged to the ETEC strain and it is the most common. While only 14 (18%) belonged to the EHEC strains Conclusion: Through these results, it was found that the most important type of bacteria that causes diarrhea in children. Prevalence of enterotoxogenic and shiga strains in Tikrit teaching hospital. The proportion of E. coli bacteria that causes diarrhea is higher than other types in animals.
Keywords: children, bacteria, diarrhea, E. coli.